Modulation by ENSO of the Relationship Between Stratospheric Sudden Warming and the Madden‐Julian Oscillation. Issue 15 (6th August 2020) - Ma, Ji; Chen, Wen; Nath, Debashis; Lan, Xiaoqing
Abstract: The ENSO modulation on the relationship between the Madden‐Julian Oscillation (MJO) and major stratospheric sudden warming (SSW) in the Northern Hemisphere winter is analyzed. The results indicate that the statistical relationship between the MJO and SSWs is robust during La Niña years but almost nonexistent during El Niño years. During La Niña years, a significant response of stratospheric temperature appears after certain MJO phases with a distribution consistent with MJO periodicity, whereas the response becomes nonsignificant during El Niño years. Further analysis indicates that ENSO influences the MJO‐related geopotential height anomalies in middle to high latitudes of the upper troposphere, which leads to an increase in wavenumber 2 in La Niña winters. And wavenumber 2 plays a key role in generating the strong heat flux anomalies in the stratosphere. The results may help to explain the more frequent occurrence of extreme events in the stratosphere, such as SSW during La Niña winters. Plain Language Summary: Stratospheric sudden warming (SSW) is the most dramatic phenomenon in the stratosphere and can exert an influence on tropospheric flow lasting for several weeks. Previous studies have documented that SSW tends to follow certain phases of the Madden‐Julian Oscillation (MJO). This relationship provides a new pathway through the stratosphere for the MJO to influence the middle to high latitudes, which may improve intraseasonal projections of the Northern Annular Mode. In this study, we show that there is a much stronger MJO‐SSW relationship during La Niña winters than El Niño winters. This close MJO‐SSW relationship is further attributable to a much stronger MJO‐related stratosphere wave activity during La Niña winters, with a major contribution from planetary wavenumber 2. And the increase in wavenumber 2 is caused by the MJO‐related geopotential height anomalies in the middle to high latitudes of the Northern Hemisphere. The results show that the intraseasonal variability of the stratosphere is sensitive to the tropical signals during La Niña winters. The results may help explain that, although the stratospheric polar vortex is stronger on a seasonal mean timescale during La Niña winters, some extreme events, such as SSWs, may not decrease as suggested in observational studies. Key Points: The MJO‐SSW relationship is much stronger during La Niña winters than during El Niño winters ENSO can affect the MJO‐related geopotential height anomalies in middle to high latitudes of the Northern Hemisphere The MJO‐related stratospheric wave activity tends to be strong during La Niña winters, due to an increase in its wavenumber 2 component